2021
DOI: 10.1073/pnas.2025275118
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine controls whether new declarative information updates reactivated memories through reconsolidation

Abstract: Consolidation and reconsolidation are independent memory processes. Consolidation stabilizes new memories, whereas reconsolidation restabilizes memories destabilized when reactivated during recall. However, the biological role of the destabilization/reconsolidation cycle is still unknown. It has been hypothesized that reconsolidation links new information with reactivated memories, but some reports suggest that new and old memories are associated through consolidation mechanisms instead. Object-recognition mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…For example, pre-training intra-hippocampal muscimol administration affects ORM only when the training-test interval is longer than 10 min [ 23 ], suggesting that the hippocampus is not required for short-term ORM recall, that other brain regions take over the role of the hippocampus in short-term ORM processing when it remains disabled for a long time, or that short-term and long-term ORM involve independent mechanisms, as it has been reported for other memory types [ 24 ]. In this regard, our data indicate that the hippocampus is key for long-term ORM formation and substantiate further the idea that the two long-term object memories acquired during training in the novel object recognition task are independent [ 13 ]. Furthermore, the fact that the animals were amnesic only for the object they were exploring when the MS was inactivated strongly indicates that theta is not just a byproduct of learning-induced neural plasticity but is functionally linked to the calculations that occur in the hippocampus during long-term ORM formation.…”
Section: Main Textsupporting
confidence: 84%
See 1 more Smart Citation
“…For example, pre-training intra-hippocampal muscimol administration affects ORM only when the training-test interval is longer than 10 min [ 23 ], suggesting that the hippocampus is not required for short-term ORM recall, that other brain regions take over the role of the hippocampus in short-term ORM processing when it remains disabled for a long time, or that short-term and long-term ORM involve independent mechanisms, as it has been reported for other memory types [ 24 ]. In this regard, our data indicate that the hippocampus is key for long-term ORM formation and substantiate further the idea that the two long-term object memories acquired during training in the novel object recognition task are independent [ 13 ]. Furthermore, the fact that the animals were amnesic only for the object they were exploring when the MS was inactivated strongly indicates that theta is not just a byproduct of learning-induced neural plasticity but is functionally linked to the calculations that occur in the hippocampus during long-term ORM formation.…”
Section: Main Textsupporting
confidence: 84%
“…To do that, we implanted electrode arrays in the dorsal CA1 region of adult male Wistar rats (3-months-old, 300–350 g) and trained them in the novel object-recognition paradigm, a long-term ORM-inducing task based on the rodents’ natural predilection for novelty that involves exposure to two different but behaviorally equivalent novel objects A and B in a familiar open field arena for 5-min (Fig. 1 a) [ 13 ]. A digital video camera fixed above the arena was utilized for tracking, recording, and analyzing the animals’ position and behavior with the ObjectScan system software (for details see Additional file 1 ).…”
Section: Main Textmentioning
confidence: 99%
“…Consistent with previous reports ( Bruce-Keller et al, 2011 ; Chen et al, 2012 ), we confirmed the deterioration of cognitive function with the increase of the age of APP/PS1 mice, which included working memory, short-term spatial memory, long-term recognition memory, and spatial learning and memory. These cognitive tasks mainly reflect the ability of hippocampus-dependent learning and memory ( Zheng et al, 2009 ; Gonzalez et al, 2021 ), and the results hinted at an abnormality of hippocampal function in APP/PS mice at 8 months of age. To exclude the effect of locomotor activity in cognitive tests, we performed OFTs and found that APP/PS1 mice showed decreased locomotor activity in the novel environment at 6 months, but not at 8 months of age.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, blocking dopamine reuptake in the insular cortex of an Alzheimer's disease mice model reversed the STM and LTM object amnesia in those mice (Guzmán-Ramos et al, 2012 ). Moreover, hippocampal dopaminergic tone is essential for object memory persistence (Neves et al, 2020 ; Vargas et al, 2020 ; Lima et al, 2022 ) and reconsolidation (Rossato et al, 2015 ; Gonzalez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%